2022
DOI: 10.1111/apel.12361
|View full text |Cite
|
Sign up to set email alerts
|

How do political connections affect the formation of zombie firms? Evidence from Chinese manufacturing listed enterprises

Abstract: Zombie firms that rely on government subsidies and bank loans have seriously affected the healthy development of economies. This paper uses data from Chinese listed manufacturing enterprises from 2007 to 2017 to test and analyse the relationship between political connections and zombie enterprises. The study finds: (i) political connections are positively correlated with the 'zombification' of enterprises; (ii) credit subsidies play an intermediary role between political connections and 'zombification' of ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is generally accepted that zombie firms are those that continue to incur losses, have no hope of reversing their deficits, and rely mainly on government subsidies or bank loans to continue their lives (McGowan et al, 2019; San‐Jose et al, 2021; Alvarez et al, 2023). From this, it can be seen that zombie firms are characterised by two features: low business performance and dependence on government and banks for survival (Shao et al, 2022). The dominant approach in economics is to identify zombie firms from the perspective of bank credit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally accepted that zombie firms are those that continue to incur losses, have no hope of reversing their deficits, and rely mainly on government subsidies or bank loans to continue their lives (McGowan et al, 2019; San‐Jose et al, 2021; Alvarez et al, 2023). From this, it can be seen that zombie firms are characterised by two features: low business performance and dependence on government and banks for survival (Shao et al, 2022). The dominant approach in economics is to identify zombie firms from the perspective of bank credit.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some enterprises appear to have normal real interest rates, but in fact, their profits are not enough to pay the interest on loans. They rely on ‘borrowing new loans to pay off old ones’ from the bank, which is not the type of zombie firms that the CHK methodology can identify (Shao et al, 2022). To compensate for the shortcomings of the CHK method, Fukuda and Nakamura (2011) added two criteria, which is referred to as the ‘FN‐CHK method’.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it could reduce productivity by allowing low-performance zombie firms. In fact, Shao et al (2022) recently found empirical evidence citing that political connections were associated with the zombification of Chinese manufacturing firms. To confirm this institutional hypothesis, in Figure 1, we plot the estimated coefficients of leverage on the vertical axis and the degree of financial access taken from the IMF Financial Development Index database on the horizontal axis.…”
Section: Nakatani | 195mentioning
confidence: 99%